2017
DOI: 10.1128/jb.00465-16
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Biological Studies of Osmotic Shock Response in Streptomyces spp

Abstract: Most bacteria are likely to face osmotic challenges, but there is yet much to learn about how such environmental changes affect the architecture of bacterial cells. Here, we report a cell-biological study in model organisms of the genus Streptomyces, which are actinobacteria that grow in a highly polarized fashion to form branching hyphae. The characteristic apical growth of Streptomyces hyphae is orchestrated by protein assemblies, called polarisomes, which contain coiled-coil proteins DivIVA and Scy, and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…Recent work suggests that hyperosmotic stress conditions affects apical growth in streptomycetes 24 Consistent with these observations, we noticed that growth was progressively disturbed in the filamentous actinomycete Kitasatospora viridifaciens , when increasing amounts of sucrose were added to the medium (Fig. 1A).…”
Section: Resultssupporting
confidence: 89%
“…Recent work suggests that hyperosmotic stress conditions affects apical growth in streptomycetes 24 Consistent with these observations, we noticed that growth was progressively disturbed in the filamentous actinomycete Kitasatospora viridifaciens , when increasing amounts of sucrose were added to the medium (Fig. 1A).…”
Section: Resultssupporting
confidence: 89%
“…At 0.6 M sucrose, the protoplasts had worse regeneration rate and the hyphal length was less uniform compared with the 0.8 M sucrose culture media. Fuchino et al [21] reported that mycelial polarization occurred more often when the hyphae grew in a lower osmotic pressure. It indicated the mycelial grew faster at lower osmotic pressure than that at higher osmotic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Our cryoET data shows that the cell wall is thinner when K. viridifaciens is exposed to hyperosmotic stress. Indeed, this would be expected given that osmotic upshifts lead to a growth arrest at the leading hyphal tip 26 . As a consequence, less nascent PG is inserted and might result in a thinner and structurally weaker cell wall.…”
Section: Discussionmentioning
confidence: 97%